Experiences of female journalists in Zimbabwean male-dominated newsrooms - Lyton Ncube (Communicare)
Baseline surveys on the gender distribution in Zimbabwe’s media industry indicate a male dominance in newsrooms in general, as well as in media leadership positions. This gender disparity reflects the persistence of patriarchy and heteronormative beliefs in the Zimbabwean society, despite the country’s constitution upholding gender mainstreaming and principles of equality. However, there is a dearth of systematic academic studies exploring the experiences, aspirations and attitudes of female journalists in these macho newsrooms. The article is theoretically guided by Raewyn Connell’s hegemonic masculinity theory. In-depth semi-structured interviews were conducted with purposively selected female Zimbabwean journalists to discuss their experiences and struggles in such environments. Findings indicate that gender remains an unresolved question in Zimbabwe. Due to alleged unprofessional conduct by some male journalists, Zimbabwean newsrooms resemble phallocentric and misogynistic “carnivals”. Women experience and battle against various forms of sexual harassment despite the presence of mechanisms to protect victims. Despite this violence, female journalists persevere and also find ways of speaking back to power.